Synthesis and Structure-Activity Relationship of 3-Chloropiperidines as Potential DNA Alkylating Agents - Kramer, Tim; Justus Liebig University Giessen (My University, 2022)
Alkylating agents have been widely used in cancer treatment since their discovery during the mid-twentieth century. Nitrogen mustards represent a subclass of these medical agents and are characterized by their unique 2-chloroethylamine moiety. This functional group enables the intramolecular formation of a highly electrophilic aziridinium ion, which is readily attacked by cellular nucleophiles such as DNA bases. The resulting covalent adducts might cause depurination and DNA strand cleavage, leading to inhibition of DNA replication and eventually apoptosis of the treated cancer cells. However, this reactivity is not limited to malignant tissue, resulting in severe side effects and therefore limited therapeutic application of these drugs. Over the last decades, several nitrogen mustard derivatives have been developed to reduce side effects and enhance their respective selectivity or cellular uptake. One example is the introduction of various aromatic nitrogen substituents instead of the early aliphatic derivatives. The electron-withdrawing effect of these aromatic moieties reduces the nucleophilicity of the nitrogen atom, consequently decreasing the rate of aziridinium ion formation and therefore lowering their reactivity. Another approach to reduce their reactivity was applied in our group by including the 2-chloroethylamine functional group into a heterocyclic piperidine system, leading to a reduced rate of aziridinium ion formation due to the increased ring strain of the emerging bicyclic system. The resulting 3-chloropieridines showed promising DNA alkylating activities in previous studies and are therefore analyzed in more detail during this work. The publications included in this work demonstrate, that the reactivity of the examined 3-chloropiperidine derivatives could be adjusted by introduction of different substituents on the nitrogen atom as well as the C5 position of the cyclic piperidine system. Further biological evaluation of mono- and bifunctional 3-chloropiperidines revealed a remarkable selectivity of aromatic nitrogen substituents for pancreatic cancer cells, which could be later attributed to an inappropriate cellular response of this specific cell line. In addition, we studied aliphatic and aromatic 3-chloropiperidines using NMR kinetic methods, revealing the importance of the C5 ring substituents. The presence or absence of the C5 geminal methylation had a significant effect towards the formation of the reactive bicyclic aziridinium intermediate, and therefore the rate-determining step of the DNA alkylation mechanism. The study also verified the bicyclic, boat-like structure of the intermediate aziridinium ions by single crystal X-ray analysis and confirmed the decreased reactivity of our cyclic compounds in comparison with aliphatic nitrogen mustards. Further investigations of the C5 geminal methylated 3-chloropierdines concluded that the acceleration of the reaction rate, compared to the corresponding unsubstituted derivatives, is a result of a classic, angle dependent Thorpe-Ingold effect. Accordingly, bulky substituents in C5 position lead to decreased internal angles and therefore accelerate the formation of the bicyclic aziridinium ion. In contrast, strained cycloalkyl substituents result in enlarged internal angles and retard the cyclization reaction. Beside the already established variation of the nitrogen substituent, this new structure-activity relationship demonstrated to be another useful tool to modulate the reactivity of 3-chloropiperidines.
Keywords: DNA Alkylating Agents; 3-Chloropiperidine; Structure-Activity Relationship; ddc:540